2003
DOI: 10.1046/j.1365-2125.2003.01895.x
|View full text |Cite
|
Sign up to set email alerts
|

Moclobemide poisoning: toxicokinetics and occurrence of serotonin toxicity

Abstract: Aims To investigate the spectrum of toxicity of moclobemide overdose, the occurrence of serotonin toxicity, and to estimate toxicokinetic parameters. Methods All moclobemide overdoses presenting over a 10-year period to the Hunter Area Toxicology Service were reviewed. Clinical features, complications, length of stay (LOS) and intensive care (ICU) admission rate were extracted from a standardized, prospectively collected database. Comparisons were made between moclobemide alone and moclobemide with a serotoner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…However, if a second serotonergic drug was ingested, serotonin toxicity was nearly always present and was severe in about half of these cases. 15 Box 1: Drugs that have been associated with moderate to severe serotonin toxicity*…”
Section: How Does It Present?mentioning
confidence: 99%
“…However, if a second serotonergic drug was ingested, serotonin toxicity was nearly always present and was severe in about half of these cases. 15 Box 1: Drugs that have been associated with moderate to severe serotonin toxicity*…”
Section: How Does It Present?mentioning
confidence: 99%
“…All three methods involved high-performance liquid chromatography (HPLC), with either ultraviolet (UV) detection [8,9] or electrospray ionisation-mass spectrometry (ESI-MS) [10]. Although a ring-opened metabolite was also reported to be measured with two of these techniques [8,9], this very compound is not of interest for pharmacokinetic studies, since its concentrations in human plasma are too low to be monitored for a required period of time [8,12], and the metabolite is therapeutically inactive (it was found to inhibit MAO-B in rat liver, but has no MAO-A inhibitory activity) [2,12]. Therefore, in all published pharmacokinetic studies that have been found in literature [3,[13][14][15][16], only plasma concentrations of moclobemide and two metabolites, Ro 12-8095 and Ro 12-5637, have been monitored.…”
Section: Introductionmentioning
confidence: 98%
“…Readers are referred to recent selected reviews of SS for a broader perspective. There have been advances in the quantification of the frequency and severity of SS with different drugs, 9‐14 in the definition of SS in animals and humans, 15‐17 in the pathophysiology, 15 in the clinical presentation, 18 and in its management and treatment 19‐21 …”
mentioning
confidence: 99%